petrographical study of Basaltic rocks in Bostan Al Hammam – Al Kadmous sheet- NW Syria - Mostafa, Mahmoud; Khaddam, Rasha (Latakia University Journal -Basic Sciences Series, 2019)
This paper Presents a Petrographic study of basalticrocks in (Bostan Al Hammam), which itis apart of the Diaeremes to theplosirelacuneQadmous district .In study, We identify the type ofCretaceous and Neogenebasalt rocks in the studied area.The basalt deposits in Bostan Al Hammam back flowto differentdate ranges: the Firstis the Limits of the Cretaceous, they are pyroclastic rocks and the volcanic tuf , andSome times pyroclastic basalt, and the secondduring the Neogene period, Particularly in Holocene time associatedwith forming Al-GAB rift and it is basalt rocks are lightgray to darkcolor composed of the following petrographic types :Olivine basalt, Plajioclase basalt.